Stilbene compound trans-3, 4, 5, 4´-tetramethoxystilbene, a potential anticancer drug, regulates constitutive androstane receptor (Car) target genes, but does not possess proliferative activity in mouse liver. (1st October 2019) - Dusek, Jan; Skoda, Josef; Holas, Ondrej; Horvatova, Alzbeta; Smutny, Tomas; Linhartova, Lenka; Hirsova, Petra; Kucera, Otto; Micuda, Stanislav; Braeuning, Albert; Pavek, Petr
Graphical Abstract: Highlights: trans -3, 4, 5, 4´-tetramethoxystilbene(TMS) is a murine Car agonist. TMS controls Car target genes involved in xenobiotic and endobiotic metabolism. TMS has limited effects on genes controlling liver proliferation. TMS stimulates apoptosis in murine hepatic AML12 cells. Abstract: The constitutive androstane receptor(CAR) activation is connected with mitogenic effects leading to liver hyperplasia and tumorigenesis in rodents. CAR activators, including phenobarbital, are considered rodent non-genotoxic carcinogens. Recently, trans -3, 4, 5, 4´-tetramethoxystilbene(TMS), a potential anticancer drug (DMU-212), have been shown to alleviate N -nitrosodiethylamine/phenobarbital-induced liver carcinogenesis. We studied whether TMS inhibits mouse Car to protect from the PB-induced tumorigenesis. Unexpectedly, we identified TMS as a murine CAR agonist in reporter gene experiments, in mouse hepatocytes, and in C57BL/6 mice in vivo . TMS up-regulated Car target genes Cyp2b10, Cyp2c29 and Cyp2c55 mRNAs, but down-regulated expression of genes involved in gluconeogenesis and lipogenesis. TMS did not change or down-regulate genes involved in liver proliferation or apoptosis such as Mki67, Foxm1, Myc, Mcl1, Pcna, Bcl2, or Mdm2, which were up-regulated by another Car ligand TCPOBOP. TMS did not increase liver weight and had no significant effect on Ki67 and Pcna labeling indices in mouse liver in vivo . In murine hepatic AML12 cells, we confirmed a Car-independent proapoptotic effect of TMS. We conclude that TMS is a Car ligand with limited effects on hepatocyte proliferation, likely due to promoting apoptosis in mouse hepatic cells, while controlling Car target genes involved in xenobiotic and endobiotic metabolism.